2007
DOI: 10.1242/jcs.03318
|View full text |Cite
|
Sign up to set email alerts
|

A new activating role for CO in cardiac mitochondrial biogenesis

Abstract: To investigate a possible new physiological role of carbon monoxide (CO), an endogenous gas involved in cell signaling and cytotoxicity, we tested the hypothesis that the mitochondrial generation of reactive oxygen species by CO activates mitochondrial biogenesis in the heart. In mice, transient elevations of cellular CO by five- to 20-fold increased the copy number of cardiac mitochondrial DNA, the content of respiratory complex I-V and interfibrillar mitochondrial density within 24 hours. Mitochondrial bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
182
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(199 citation statements)
references
References 50 publications
(47 reference statements)
9
182
2
3
Order By: Relevance
“…HO‐1 can induce mitophagy pathways through nuclear respiratory factor‐dependent (NRF‐1‐dependent) expression of the PINK1/PARK2 genes, as demonstrated recently by Suliman, Keenan, and Piantadosi (2017). This effect extends the described activation of mitochondrial biogenesis by CO produced by HO‐1 (Suliman, Carraway, Tatro, & Piantadosi, 2007). Nevertheless, we observed a decreased expression of NRF‐1 in fibroblasts from COPD patients treated with hemin, suggesting that another mechanism could be involved.…”
Section: Discussionsupporting
confidence: 85%
“…HO‐1 can induce mitophagy pathways through nuclear respiratory factor‐dependent (NRF‐1‐dependent) expression of the PINK1/PARK2 genes, as demonstrated recently by Suliman, Keenan, and Piantadosi (2017). This effect extends the described activation of mitochondrial biogenesis by CO produced by HO‐1 (Suliman, Carraway, Tatro, & Piantadosi, 2007). Nevertheless, we observed a decreased expression of NRF‐1 in fibroblasts from COPD patients treated with hemin, suggesting that another mechanism could be involved.…”
Section: Discussionsupporting
confidence: 85%
“…Protection by HO-1 requires Akt1, as mtDNA was not protected in DOX-treated cells preincubated with Akt inhibitor (Akt8; data not shown) or cells transfected with HO-1 and treated with Akt inhibitor (Akt8) before DOX ( Figure 7B). It has been demonstrated that HO-1 activates GC and that cGMP is involved in CO-activating mitochondrial biogenesis in these cells (16). In the present studies, losses in cellular mtDNA content after DOX correlated negatively with cell viability (P < 0.01; r 2 = -0.7).…”
Section: Figuresupporting
confidence: 56%
“…Mitochondrial fluorescence intensity was enhanced by CO treatment, and the 2-dose protocol prevented the loss of fluorescence after DOX. The distribution of GFP also substantiated mitochondrial proliferation morphologically after CO treatment, as multiple new fluorescent aggregates that appeared within the cardiomyocytes were confirmed by EM as having mitochondrial structure (16).…”
Section: Figurementioning
confidence: 59%
See 2 more Smart Citations